Calculation:

In \(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\)

\(\displaystyle\angle{B}{A}{C}=\angle{E}{D}{F}\)

\(\displaystyle\angle{A}{B}{C}=\angle{D}{E}{F}\)

\(\displaystyle\angle{B}{C}{A}=\angle{E}{F}{D}\)

\(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\) are similar.

In \(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\)

\(\displaystyle\angle{B}{A}{C}=\angle{E}{D}{F}\)

\(\displaystyle\angle{A}{B}{C}=\angle{D}{E}{F}\)

\(\displaystyle\angle{B}{C}{A}=\angle{E}{F}{D}\)

\(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\) are similar.